Heart failure associated with imported malaria: a nationwide Danish cohort study. (27th July 2021) - Brainin, Philip; Mohr, Grimur Høgnason; Modin, Daniel; Claggett, Brian; Silvestre, Odilson M.; Shah, Amil; Vestergaard, Lasse S.; Jensen, Jens Ulrik Stæhr; Hviid, Lars; Torp‐Pedersen, Christian; Køber, Lars; Solomon, Scott; et al.
Abstract: Aims: Despite adequate treatment, recent studies have hypothesized that malaria may affect long‐term cardiovascular function. We aimed to investigate the long‐term risk of cardiovascular events and death in individuals with a history of imported malaria in Denmark. Methods: Using nationwide Danish registries, we followed individuals with a history of malaria for the risk of incident heart failure (HF), myocardial infarction (MI), cardiovascular death and all‐cause death (1 January 1994 to 1 January 2017). The population was age‐ and sex‐matched with individuals without a history of malaria from the Danish population (ratio 1:9). We excluded patients with known HF and ischaemic heart disease at inclusion. Results: We identified 3912 cases with a history of malaria (mean age 33 ± 17 years, 57% male, 41% Plasmodium falciparum infections). The median follow‐up was 9.8 years (interquartile range 3.9–16.4 years). Event rates per 1000 person‐years for individuals with a history vs. no history of malaria were HF: 1.84 vs. 1.32; MI: 1.28 vs. 1.30; cardiovascular death: 1.40 vs. 1.77; and all‐cause death: 5.04 vs. 5.28. In Cox proportional hazards models adjusted for cardiovascular risk factors, concomitant pharmacotherapy, region of origin, household income and educational level, malaria was associated with HF (HR: 1.59 [1.21–2.09], P = 0.001), but not MI (HR: 1.00 [0.72–1.39], P = 1.00), cardiovascular death (HR: 1.00 [0.74–1.35], P = 0.98) or all‐cause death (HR 1.11 [0.94–1.30], P = 0.21). Specifically, P. falciparum infection was associated with increased risk of HF (HR: 1.64 [1.14–2.36], P = 0.008). Conclusion: Individuals with a history of imported malaria, specifically P. falciparum, may have an increased risk of incident HF.